Electrochemical Fabrication of Metal/Organic/Metal Junctions for Molecular Electronics and Sensing Applications - Dasari, Radhika (2011)
A simple electrochemical approach was used for fabricating electrode/metal nanowire/(molecule or polymer)/electrode junctions for sensing or molecular electronics applications.The procedure for fabricating these molecule-based devices involves electropolymerization of phenol or chemisorption of alkanethiols on one set of electrodes (E1) and electrodeposition of Ag metal nano/microwires on a second electrode (E2) which is ∼5 μm away from E1. Under appropriate deposition conditions, Ag nanowires grow from E2 and cross over to E1, forming a E1/(molecule or polymer)/Ag nanowire (NW)/E2 junction. The junction resistance was controlled by (1) electrodepositing polyphenol of varied densities on E1 and (2) assembling alkanethiols of different chain lengths on E1. Ag NWs at high resistance E1/polyphenol/Ag NW/E2 junctions functionalized with Pd monolayer protected clusters (MPCs) responded fast and reversibly to H2 concentrations as low as 0.11% in a nitrogen carrier gas by a resistance decrease, likely due to volume expansion of the Pd nanoparticles, demonstrating the use of these electrochemically fabricated junctions for gas sensing applications.